Stress analysis of thin-walled laminated composite beams - Mohamed Ali, Jaafar Syed; Hrairi, Meftah; Mohamad, Masturah (Asian Research Publishing Network (ARPN), 2015)
An educational software which can aid students in stress analysis of thin wall open sections made of composite material has been developed. The software enables students to easily calculate stresses of thin wall open section and evaluate the stresses in each ply. Results obtained through this software have been validated against ANSYS V14. The software is intended to be used as a resourceful tool for effective teaching and learning process on thin-walled structures, aircraft structures and composite structures courses.